1980
DOI: 10.1002/jcp.1041050211
|View full text |Cite
|
Sign up to set email alerts
|

Tumor promoter modulation of epidermal growth factor‐ and nerve growth factor‐induced adhesion and growth factor binding of PC‐12 pheochromocytoma cells

Abstract: Nerve growth factor (NGF) has previously been shown to increase the rate of adhesion of PC-12 pheochromocytoma cells to cell culture dishes. This increase in the rate of adhesion was postulated to be important in NGF-mediated neurite outgrowth. We now report that epidermal growth factor (EGF) is also able to increase the rate of adhesion of PC-12 cells to cell culture dishes, but does not elicit neurite outgrowth. The dose-response curve for EGF is bell-shaped, in contrast to the more classically shaped dose-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
35
2

Year Published

1983
1983
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 28 publications
3
35
2
Order By: Relevance
“…Tumor promoters inhibit EGF-induced mitogenesis in human fibroblasts (34), rat hepatoma cells (29), and human hepatoma cells (37) and block EGF-induced cellular adhesion in PC12 phaeochromocytoma cells (8) and EGF-induced production of diacylglycerol in A431 cells (43). We confirm that TPA can inhibit EGF-induced mitogenesis in human fibroblasts and present a possible mechanism.…”
supporting
confidence: 72%
“…Tumor promoters inhibit EGF-induced mitogenesis in human fibroblasts (34), rat hepatoma cells (29), and human hepatoma cells (37) and block EGF-induced cellular adhesion in PC12 phaeochromocytoma cells (8) and EGF-induced production of diacylglycerol in A431 cells (43). We confirm that TPA can inhibit EGF-induced mitogenesis in human fibroblasts and present a possible mechanism.…”
supporting
confidence: 72%
“…In addition to the alterations in surface morphology of sympathetic neurons, a threefold increase in the number of coated pits per unit area of cell surface was seen after NGF treatment (3) . In another study, PC 12 cells are reported to undergo loss ofshort microvilli and an increase in long microvilli after 1-h treatment with NGF or EGF (4) .…”
mentioning
confidence: 92%
“…The first purpose of the present study was to determine whether the observed surface changes were specific manifestations of early differentiation or reflected a more universal phenomenon associated with the early response of sensitive cells to peptide growth factor treatment . To deal with this question, we chose to take advantage ofthe observation that PC12 cells have receptors for, and responses to, both NGF and EGF (4,8). These cells respond to NGF in various ways including cessation of cell division (5) and neuronal differentiation (5-7), as noted above, and respond to EGF with ornithine decarboxylase induction (8), rapid phosphorylation of several proteins (9), continued cell division, and no evident morphological differentiation (4,8) .…”
mentioning
confidence: 99%
“…Although the effect of this factor on PC12 cells is proliferative rather than differentiative, it displays several properties in common with NGF (28). When PC12 cells were treated with EGF or NGF at concentrations maximally effective in stimulating transcription of various NGF-induced genes (5 ng/ml and 100 ng/ml, respectively; ref.…”
mentioning
confidence: 99%